Biochemical and Structural Insights into FIH‐Catalysed Hydroxylation of Transient Receptor Potential Ankyrin Repeat Domains. (9th January 2023) - Saward, Benjamin G.; Leissing, Thomas M.; Clifton, Ian J.; Tumber, Anthony; Timperley, Christopher M.; Hopkinson, Richard J.; Schofield, Christopher J.
Abstract: Transient receptor potential (TRP) channels have important roles in environmental sensing in animals. Human TRP subfamily A member 1 (TRPA1) is responsible for sensing allyl isothiocyanate (AITC) and other electrophilic sensory irritants. TRP subfamily vanilloid member 3 (TRPV3) is involved in skin maintenance. TRPV3 is a reported substrate of the 2‐oxoglutarate oxygenase factor inhibiting hypoxia‐inducible factor (FIH). We report biochemical and structural studies concerning asparaginyl hydroxylation of the ankyrin repeat domains (ARDs) of TRPA1 and TRPV3 catalysed by FIH. The results with ARD peptides support a previous report on FIH‐catalysed TRPV3 hydroxylation and show that, of the 12 potential TRPA1 sequences investigated, one sequence (TRPA1 residues 322–348) undergoes hydroxylation at Asn336. Structural studies reveal that the TRPA1 and TRPV3 ARDs bind to FIH with a similar overall geometry to most other reported FIH substrates. However, the binding mode of TRPV3 to FIH is distinct from that of other substrates. Abstract : Confirmation analysis : Following the differing conclusions of previous studies, we report biochemical and structural studies on asparaginyl hydroxylation of the ankyrin repeat domains of human transient receptor potential channels TRPA1 and TRPV3 as catalysed by the 2‐oxoglutarate oxygenase factor inhibiting hypoxia‐inducible factor (FIH).